Missing Pieces: The Stunting Challenges by Single Mothers in Indonesia - Khusaini, Moh.; Fazaalloh, Al Muizzuddin; Finuliyah, Firdaus (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
Child stunting remains a significant health issue in Indonesia, particularly within single-mother households facing socioeconomic challenges. This study aims to analyze the impact of single-mother status on child stunting prevalence while evaluating other socioeconomic factors such as educational level, poverty status, and access to basic facilities. The research employs descriptive statistics, multinomial logistic regression, and binary logistic regression methods with SUSENAS 2022. The findings reveal that single-mother status, especially in the divorced while living and divorced due to death categories, significantly increases the risk of child stunting. Additionally, factors such as low maternal education, employment in informal sectors, and limited access to proper sanitation increase stunting prevalence. This study highlights the urgency of integrated policies to support single mothers through improved education, access to stable employment, and enhanced infrastructure to reduce stunting and improve the quality of life for children in vulnerable households. Furthermore, to improve the quality of life of children in each household, debriefing related to nutrition can be carried out for mothers. Thus, problems related to the prevalence of stunting can be minimized, especially from single mothers.